2008
DOI: 10.1111/j.1399-0012.2008.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in southern Chinese renal‐transplant recipients

Abstract: Chinese renal transplant recipients face a high risk of TB because of their immuno-compromised state and epidemiological prevalence of the disease. Therefore, attention should be given to this differential diagnosis in clinical practice. Balancing the benefits and disadvantages of anti-tuberculosis chemotherapy is of importance for this specific population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 8 publications
1
30
4
Order By: Relevance
“…It continues to be the most common form in kidney transplant recipients [29]. Pulmonary signs were observed in 37,5% of the cases particularly coughing (12,5 % of the patients) versus 56.1% in literature accompanied by spittles in 39 % of the cases [26]. No case of hemoptysis was reported in our study while they are observed in 20 % in other studies [30].…”
Section: Disscussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It continues to be the most common form in kidney transplant recipients [29]. Pulmonary signs were observed in 37,5% of the cases particularly coughing (12,5 % of the patients) versus 56.1% in literature accompanied by spittles in 39 % of the cases [26]. No case of hemoptysis was reported in our study while they are observed in 20 % in other studies [30].…”
Section: Disscussioncontrasting
confidence: 51%
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9 % in literature [4,25,26,27]. Impairment of the general state was observed in 31,2% patients in our study versus 40 % in literature [27,28].…”
Section: Disscussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…1,8,9 Seven of the patients in our study were successfully treated by rifampicin-included quartet of therapy for a median duration of 9 months. All had well-functioning allografts.…”
Section: Discussionmentioning
confidence: 99%
“…4 In accordance with our result, data from Southern China and Thailand, where TB epidemicity was also high, demonstrated prevalence rates ranging from 1.76% to 12.96%. 8,9 Diagnosis of TB depends on demonstration of acidfast bacilli in study materials, cultivating the microorganism in special media, and presence of caseating granuloma with or without acid-fast bacilli in histological specimens. The tuberculin skin test, on the other hand, is a screening test to reveal the history of contact with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%